Application of Radio Frequency Identification as a Motorcycle Quality Check Card - Indrayana, Didik; Prajoko (Jurnal Sistem Informasi (JASISFO), 2022)
Radio Frequency Identification (RFID) is a wireless communication consisting of 2 (two) tag components and a reader or reader to uniquely identify an object. A reader or reader is a device that has one or more antennas that transmit radio waves and receive signals back from the tag. RFID. In the application of RFID, most use a serial number to store an object’s identity on a microchip and are usually equipped with an antenna, where the antenna and chip are RFID tags. The antenna used and the chip communicate information for identification to the reader or what is known as the reader, then the reader or reader converts the reflected radio waves of the RFID tag into digital information. The application of Radio Frequency Identification (RFID) is intended to assist the process of testing the quality of Honda motorbikes or PDI (pre-delivery inspection) where this is part of the SOP (standard operating procedure) before the motorbike is distributed to consumers to ensure the quality of the motorbike is maintained. The inspections carried out include the outside of the motor and then the inside, below, then testing when the motor is running, the availability of equipment or tools, and equipment documents such as service books and maintenance instructions. Whereas the previous process still uses paper cards which will be discarded when a consumer receives the motor. Applications made using the application of Radio Frequency Identification (RFID) in the form of a card will replace the use of paper when conducting a motor quality inspection.